Palladium(II) Complexes Containing Mixed Nitrogen-Sulphur Donor Ligands: Interaction of [Pd(Methionine Methyl Ester)(H2O)2]2+ with Biorelevant Ligands - Mohamed M. Shoukry; Sameya M. T. Ezzat (Bioinorganic Chemistry and Applications)
Pd(MME)Cl2 complex (MME = methionine methyl ester) was synthesised and characterized by physicochemical measurements. The reaction of [Pd(MME)(H2O)2]2+ with amino acids, peptides, or dicarboxylic acids was investigated at 25°C and 0.1 M ionic strength. Amino acids and dicarboxylic acids form 1 : 1 complexes. Peptides form both 1 : 1 complexes and the corresponding deprotonated amide species. The stability of the complexes formed was determined and the binding centres of the ligands were assigned. Effect of solvent on the stability constant of Pd(MME)-CBDCA complex, taken as a representative example, shows that the complex is more favoured in a medium of low dielectric constant. The concentration distribution diagrams of the complexes were evaluated.